Predictive Value of Plasma Big Endothelin-1 in Adverse Events of Patients With Coronary Artery Restenosis and Diabetes Mellitus: Beyond Traditional and Angiographic Risk Factors - Ma, Yue; Tian, Tao; Wang, Tianjie; Wang, Juan; Guan, Hao; Yuan, Jiansong; Song, Lei; Yang, Weixian; Qiao, Shubin (Frontiers in Cardiovascular Medicine, 2022)
Background: Diabetes patients are a high-risk group for coronary in-stent restenosis (ISR), so it would be valuable to identify biomarkers to predict their prognosis. The plasma big endothelin-1 (big ET-1) level is closely related to cardiovascular adverse events; however, for patients with ISR and diabetes who undergo percutaneous coronary intervention (PCI), whether big ET-1 is independently correlated with prognosis is still uncertain. Methods: Patients with drug-eluting stent (DES) restenosis who underwent successful re-PCI from January 2017 to December 2018 at the Chinese Academy of Medical Sciences Fuwai Hospital were enrolled and followed up for 3 years. The patients were divided into the tertiles of baseline big ET-1. The primary endpoints were major adverse cardiovascular events (MACEs): cardiac death, nonfatal myocardial infarction (MI), target lesion revascularization (TLR), and stroke. A Cox multivariate proportional hazard model and the C statistic were used to evaluate the potential predictive value of big ET-1 beyond traditional and angiographic risk factors. Results: A total of 1574 patients with ISR were included in this study, of whom 795 were diabetic. In patients with ISR and diabetes, after an average follow-up of 2.96±0.56 years, with the 1st tertile of big ET-1 as a reference, the HR (95% CI) of MACEs after adjustment for traditional and angiographic risk factors was 1.24 (0.51-3.05) for the 2nd tertile and 2.60 (1.16-5.81) for the 3rd. Big ET-1 improved the predictive value for MACEs over traditional risk factors (C statistic: 0.64 vs. 0.60, p=0.03). Big ET-1 was not significantly associated with the risk of MACEs in patients without diabetes. Conclusion: Elevated plasma big ET-1 was associated with a higher risk of adverse cardiovascular prognosis independently of traditional and angiographic risk factors, and therefore might be used as a predictive biomarker, in patients with ISR and diabetes.